Risk factors associated with the coexistence of stunting, underweight, and wasting in children under 5 from 31 sub-Saharan African countries - Eric Duku; Bright Opoku Ahinkorah; Abdul-Aziz Seidu; Richard Gyan Aboagye; Collins Adu; Iddrisu Amadu; James Boadu Frimpong; John Elvis Hagan Jnr.; Belinda Ampah (BMJ Open)
Objective This study investigated the risk factors associated with the coexistence of stunting, underweight, and wasting among children under age 5 in sub-Saharan Africa (SSA).Design Data of 127, 487 under-5 children from 31 countries in SSA were pooled from the Demographic and Health Surveys collected between 2010 and 2019. We examined the risk of coexistence of stunting, underweight, and wasting using multinomial logistic regression models. The results were presented using relative risk ratios (RRR) with corresponding confidence intervals (CIs).Setting Thirty-one sub-Saharan African countries.Participants Children under age 5.Outcome measures The outcome variables were three child anthropometrics: stunting (height-for-age z-scores); underweight (weight-for-age z-scores) and wasting (weight-for-height z-scores).Results The prevalence of coexistence of stunting, underweight, and wasting varied across countries, with the highest (12.14%) and lowest (0.58%) prevalences of coexistence of stunting, underweight and wasting in Benin and Gambia respectively. The risk of coexistence of the three indicators of undernutrition was higher among children aged 1 year (RRR=3.714; 95% CI 3.319 to 4.156) compared with those aged 0. The risk of coexistence of the three dimensions was lower among female children (RRR=0.468 95% CI 0.420 to 0.51), but higher for those with small size at birth (RRR=3.818; CI 3.383 to 4.308), those whose mothers had no education (RRR=3.291; 95% CI 1.961 to 5.522), not working (RRR=1.195; 95% CI 1.086 to 1.314), had no antenatal visits during pregnancy (RRR=1.364; 95% CI 1.20 to 1.541), children delivered at home (RRR=1.372; CI 1.232 to 1.529), those from poor households (RRR=1.408; 95% CI 1.235 to 1.605), those whose mothers had no access to media (RRR=1.255; 95% CI 1.144 to 1.377) and living in households with an unimproved toilet facility (RRR=1.158; 95% CI 1.032 to 1.300).Conclusions Findings suggest the urgent need for consideration of the coexistence of stunting, wasting and underweight among under-5 children in policy design and programming of interventions to eradicate child malnutrition in SSA. In the short-term, national-level policies and interventions need to be well tailored considering the compositional characteristics.